A comparison of geometric imperfection models for collapse analysis of ship-type stiffened plated grillages. (1st January 2022) - Li, Shen; Georgiadis, Dimitris G.; Kim, Do Kyun; Samuelides, Manolis S.
Highlights: Influence of geometric imperfection on the collapse analysis of stiffened plated structures. Deterministic and probabilistic geometric imperfections are compared. Multi-frame and multi-bay ship-type grillages are tested. Abstract: The assessment of the buckling and ultimate collapse strength is a mandatory step in the ultimate limit state design of ship structures. The collapse analysis of ship-type stiffened panels under longitudinal compression is highly affected by initial geometric imperfection. Several geometric imperfection models are available in the literature. Broadly speaking, they can be categorised into deterministic and probabilistic approaches. The deterministic approach describes the initial deflection field with a presumed geometric shape and a characteristic maximum distortion magnitude. Several geometric deflection shapes are commonly adopted, including hungry-horse (HH) mode, Admiralty Research Establishment (ARE) mode and critical buckling (CM) mode. Each of these deflection mode shapes is used in conjunction with a characteristic maximum distortion magnitude. Except otherwise specified, an average-level magnitude is usually applied. By contrast, the probabilistic approach evaluates the initial geometric imperfection as a random field, generated based on the prescribed statistics. A comparative study is presented in this study in the light of analysing the uncertainty in ultimate compressive strength of stiffened plated grillages induced by different modelling of geometric imperfection. In addition, the influence of relative deflection in the adjacent panels is analysed. Recommendations for choosing an imperfection model for buckling analysis of ship-type stiffened plated structures are reported.